Developing a bioethics curriculum for medical students from divergent geo-political regions. Issue 1 (December 2016) - Greenberg, Rebecca; Kim, Celine; Stolte, Helen; Hellmann, Jonathan; Shaul, Randi; Valani, Rahim; Scolnik, Dennis
Abstract Background The World Health Organization calls for stronger cross-cultural emphasis in medical training. Bioethics education can build such competencies as it involves the conscious exploration and application of values and principles. The International Pediatric Emergency Medicine Elective (IPEME), a novel global health elective, brings together 12 medical students from Canada and the Middle East for a 4-week, living and studying experience. It is based at a Canadian children's hospital and, since its creation in 2004, ethics has informally been part of its curriculum. Our study sought to determine the content and format of an ideal bioethics curriculum for a culturally diverse group of medical students. Methods We conducted semi-structured interviews with students and focus groups with faculty to examine the cultural context and ethical issues of the elective. Three areas were explored: 1) Needs Analysis - students' current understanding of bioethics, prior bioethics education and desire for a formal ethics curriculum, 2) Teaching formats - students' and faculty's preferred teaching formats, and 3) Curriculum Content - students' and faculty's preferred subjects for a curriculum. Results While only some students had received formal ethics training prior to this program, all understood that it was a necessary and desirable subject for formal training. Interactive teaching formats were the most preferred and truth-telling was considered the most important subject. Conclusions This study helps inform good practices for ethics education. Although undertaken with a specific cohort of students engaging in a health-for-peace elective, it may be applicable to many medical education settings since diversity of student bodies is increasing world-wide.